Are statins toxic or safe for kidney diseases? An updated mini-review study - Shadi Botshekan; Banafsheh Yalameha (Society of Diabetic Nephropathy Prevention, 2020)
Statins, as the most important cholesterol-lowering agents, inhibit the production of blood cholesterol by blocking an enzyme called the 3-hydroxy-3-methylglutaryl coenzyme A (HMG-COA) reductase. Statins have beneficial effects in some tissues during various injuries. Recent evidence suggests that unlike the beneficial effects of statins, administration of high doses of these drugs may increase renal impairment, although more research is needed in this regard. Therefore, this study aimed to evaluate the possible effect of different doses of statins on the morphology and function of the kidney tubular cells.